2001
DOI: 10.1590/s0104-79302001000100009
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effect of brazilian propolis on Candida albicans and Candida tropicalis

Abstract: Recently, propolis has been attracting the attention of researchers due to various biological activities and therapeutic properties. In Brazil, propolis is produced all year long, so there may be some seasonal variations. This work was carried out in order to compare propolis collected during the four seasons by its in vitro antimicrobial activity on yeast pathogens isolated from human infections. Propolis was produced by africanized honeybees in Botucatu, São Paulo State, collected throughout a year and poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1
13

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 3 publications
6
48
1
13
Order By: Relevance
“…18 Although the six samples were collected during different months, over the period of one year, no variation was observed in the chemical composition 19 nor in the antimicrobial activity 20,21 of samples of propolis from the Southeast of Brazil collected in different seasons. Therefore, although it was expected that the same basic composition would be found in the six samples analyzed, the results of each sample have been reported separately and the results compared only within each sample, for the sake of precision.…”
Section: Resultsmentioning
confidence: 99%
“…18 Although the six samples were collected during different months, over the period of one year, no variation was observed in the chemical composition 19 nor in the antimicrobial activity 20,21 of samples of propolis from the Southeast of Brazil collected in different seasons. Therefore, although it was expected that the same basic composition would be found in the six samples analyzed, the results of each sample have been reported separately and the results compared only within each sample, for the sake of precision.…”
Section: Resultsmentioning
confidence: 99%
“…Sin embargo, una de las limitaciones del propóleo es su variabilidad en composición y acción como consecuencia de variaciones en la flora de la región donde es producido, pero de acuerdo con Bankova et al (2002) (3), la acción antibacteriana siempre estará presente porque es de vital importancia como agente antimicrobiano de las abejas, independientemente de la región donde el propóleo es producido. Sin embargo, según Sforcin et al (22), en un reciente estudio, no encontró efectos diferentes debido a la estación de recolección en el propóleo. Otra de las posibles limitaciones en el uso del EEP sería su toxicidad aunque no hay estudios que afirmen o refuten su biocompatibilidad en la Estomatología.…”
Section: Resultsunclassified
“…Martinez Garcia et al (14) ;Duailibe et al (15) Clinical -Antimicrobial action Azevedo et al (4) ;Santos et al (11) ; Lofuto et al (35) Clinical -Therapeutic action in wound healing Peruchi et al (2) ;Park et al (3) ;Vargas et al (5) ; Fernandes Júnior et al (6) ; Silva et al (7) ;Sforcin et al (8) ; Sforcin et al (9) ;Oliveira et al (10) ; Auricchio et al (35) ; Fernandes Júnior et al (17) ;Machado et al (18) ;Longhini et al (19) ;Sawaya et al (20) ;Fernandes et al (21) ;Fernandes Júnior et al ( 22) ; Muli et al (23) ;Gebara et al (24) ;Fernandes Júnior et al (25) ;Bianchini et al (26) ;Gonçales et al (27) ;Dantas et al (28) ; Ayres et al (29) ;Orsi et al (30) ;Orsi et al (31) ;Sforcin et al (32) ;Sforcin et al (33) ;Orsi et al (34) ; Fernandes Júnior et al (36) ;Fernandes et al (37) ; Araújo et al (38) Experimental -Antimicrobial action Rahal et al (16) Experimental -Therapeutic action in wound healing (1) . Another study, which used propolis ointment on 22 chronic wounds, of which 11 were venous ulcers, seven pressure ulcers, two diabetic ulcers, and two post-trauma injuries, found that necrotic tissue was present in 14 (8.2%) during tissue assessment process.…”
Section: Thematic Focus Approachmentioning
confidence: 99%
“…These properties are found to be associated with its chemical composition, which has, until this moment, about 200 compounds already identified, of which the main groups are flavonoids, fat acids, alcohols, amino acids, vitamins and minerals (2,(4)(5)(6)(7)(8)(9)(10)(11) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation